Polymorphic analysis of the OsHKT1;5 exon 1 gene region on seasonal rice varieties with salt tolerant capacity - THI PHA NGUYEN; HOANG TRUC NGAN LA; TAN KHANG DO; DINH GIOI TRAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nguyen TP, La HTG, Do TK, Tran DG. 2023. Polymorphic analysis of theOsHKT1;5exon 1 gene region on seasonal rice varieties with salt tolerant capacity. Biodiversitas 24: 4159-4165. In recent years, saline intrusion has caused serious damage to agricultural production in the Mekong Delta; therefore, research on salinity-tolerant rice varieties is necessary. This study was carried out to screen the salt tolerance capacity of 38 seasonal rice varieties in four concentrations of NaCl supplements, including 4‰, 6‰, 8‰, and 10‰ in comparison with IR28 and Pokkali checks according to IRRI (2021) methods. Eight rice cultivars in four levels of salinity tolerance (two varieties of each level) were selected to evaluate the nucleotide sequence polymorphism in the coding region of OsHKT1;5exon 1, comparedwith that of IR28 and Pokkali checkcultivars and Nipponbare referential variety. The results of salt tolerance screening showed that the salt concentration and the rate of reduction of plant height and root length were positively correlated. Nucleotide sequence polymorphism analysis of OsHKT1;5exon 1 indicated six nucleotide substitutions (SNP) at positions 382, 418, 551, 994, 1119, and 1152. Further analysis revealed thatfive SNPs were detected withthree missense mutations (P60A, R63H, and H255D) in salt tolerant check variety (Pokkali), three to four SNPs with one to two missense mutations H255D or P60A and H255D were observed in salt moderate tolerant varieties, while salt-sensitive varieties and sensitive check variety IR28 were observed with two SNPs and one missense mutation (H255D).